Brucella abortus invasion of osteocytes modulates connexin 43 and integrin expression and induces osteoclastogenesis via receptor activator of NF-κB ligand and tumor necrosis factor alpha secretion - Pesce Viglietti, Ayelén Ivana (2015)
Osteoarticular brucellosis is the most common localization of human active disease. Osteocytes are the most abundant cells of bone. They secrete factors that regulate the differentiation of both osteoblasts and osteoclasts during bone remodeling. The aim of this study is to determine if Brucella abortus infection modifies osteocyte function. Our results indicate that B. abortus infection induced matrix metalloproteinase 2 (MMP-2), receptor activator for NF-κB ligand (RANKL), proinflammatory cytokines, and keratinocyte chemoattractant (KC) secretion by osteocytes. In addition, supernatants from B. abortus-infected osteocytes induced bone marrow-derived monocytes (BMM) to undergo osteoclastogenesis. Using neutralizing antibodies against tumor necrosis factor alpha (TNF-α) or osteoprotegerin (OPG), RANKL's decoy receptor, we determined that TNF-α and RANKL are involved in osteoclastogenesis induced by supernatants from B. abortus-infected osteocytes. Connexin 43 (Cx43) and the integrins E11/gp38, integrin-α, integrin-β, and CD44 are involved in cell-cell interactions necessary for osteocyte survival. B. abortus infection inhibited the expression of Cx43 but did not modify the expression of integrins. Yet the expression of both Cx43 and integrins was inhibited by supernatants from B. abortus-infected macrophages. B. abortus infection was not capable of inducing osteocyte apoptosis. However, supernatants from B. abortus-infected macrophages induced osteocyte apoptosis in a dose-dependent manner. Taken together, our results indicate that B. abortus infection could alter osteocyte function, contributing to bone damage.